Myco-biorefinery approaches for food waste valorization: Present status and future prospects - Awasthi, Mukesh Kumar; Harirchi, Sharareh; Sar, Taner; VS, Vigneswaran; Rajendran, Karthik; Gómez-García, Ricardo; Hellwig, Coralie; Binod, Parameswaran; Sindhu, Raveendran; Madhavan, Aravind; Kumar, A. N. Anoop; Kumar, Vinod; et al. (Elsevier, 2022)
Increases in population and urbanization leads to generation of a large amount of food waste (FW) and its effective waste management is a major concern. But putrescible nature and high moisture content is a major limiting factor for cost effective FW valorization. Bioconversion of FW for the production of value added products is an eco-friendly and economically viable strategy for addressing these issues. Targeting on production of multiple products will solve these issues to greater extent. This article provides an overview of bioconversion of FW to different value added products.
Keywords: Biorefinery; Waste valorization; Food waste; Fungi; Bioconversion